Transfusion-Transmitted Zika Virus Infection in Pregnant Mice Leads to Broad Tissue Tropism With Severe Placental Damage and Fetal Demise - Tai, Wanbo; Voronin, Denis; Chen, Jiawei; Bao, Weili; Kessler, Debra A.; Shaz, Beth; Jiang, Shibo; Yazdanbakhsh, Karina; Du, Lanying (Frontiers in Microbiology, 2019)
Zika virus (ZIKV) infection during pregnancy can cause significant problems, particularly congenital Zika syndrome. Nevertheless, the potential deleterious consequences and associated mechanisms of transfusion-transmitted ZIKV infection on pregnant individuals and their fetuses and babies have not been investigated. Here we examined transmissibility of ZIKV through blood transfusion in ZIKV-susceptible pregnant A129 mice. Our data showed that transfused-transmitted ZIKV at the early infection stage led to significant viremia and broad tissue tropism in the pregnant recipient mice, which were not seen in those transfused with ZIKV-positive (ZIKV+) plasma at later infection stages. Importantly, pregnant mice transfused with early-stage, but not later stages, ZIKV+ plasma also exhibited severe placental infection with vascular damage and apoptosis, fetal infection and fetal damage, accompanied by fetal and pup death. Overall, this study suggests that transfusion-related transmission of ZIKV during initial stage of infection, which harbors high plasma viral titers, can cause serious adverse complications in the pregnant recipients and their fetuses and babies.